Ein Jahr Im Krieg
Living conditions in Sarajevo one year in the war. It contains very vivid footage of human suffering endured in Sarajevo. The UN is shown to be ineffective in helping the people because they are forced to spend more time defending themselves then delivering aid. Extensive footage of the war tragedy is available. The report shows wounded and killed children in hospitals, people collecting branches to heat their homes, people cooking outside, Muslim women fighters, a secret ammunition fabric, and individuals running through the streets to escape snipers